Micromorphology and leaf ecological anatomy of Bassia halophyte species (Amaranthaceae) from Iran - Safiallah, Somayeh; Hamdi, Seyed Mohammad Mahdi; Grigore, Marius-Nicusor; Jalili, Sara (Acta Biologica Szegediensis, 2017)
Bassia belongs to the family Chenopodiaceae, which is widely distributed in the world, especially in Irano-Turanian Region. According to the morphological similarities among the species of the genus, ecological implications of structural features were studied. In fact, understanding these relationships is of great importance in natural classification. We have studied the relationships of Bassia species using morphological, anatomical, and micro-morphological methods. The current results indicated that phenotypic plasticity and repetitive patterns were probably due to ecological adaptations, especially in decreasing the leaf surface by changing the inner structure. All species have a Kranz anatomy structure (Kochioid subtype), related to C4 photosynthesis. The changes in cell size increasing the cell membrane thickness, the density of two-vascular systems, the increase of palisade to water storage parenchyma ratio and photosynthetic system. The leaf surface is covered with long highly dense hairs and microechinate ornamentation. Though the adaptation caused some morphological similarities, the variation was seen in other descriptive characteristics such as morphological and anatomical features especially in two synonym species of B. turkestanica and B. pilosa. Information about the similarity species is provided.